A descriptive study on the knowledge and practices on oral health of barangay health workers in Calamba City, Laguna - Claracay, Weby C.
This study about determining the knowledge and practices on oral health of Barangay Health Workers in Calamba City, Laguna would be a vehicle for mobility and it shapes the nation's future as it is the primary step towards having barangay health workers (BHW's) become aids in attaining better oral health for Filipinos nationwide. It aims to determine the sociodemographic profile of the BHW's in Calamba City, Laguna and also to determine their knowledge and practices on oral health. In this study, the researchers used a descriptive type of design and used the stratified random sampling design for determining the participants. Self-administered questionnaires were given to the participants and an interview was also conducted. To information gathered was tallied and the recorded scores were tabulated and their percentages were calculated. The results showed that the knowledge on oral health of the BHW's were not greatly influenced by their educational attainment. All of them answered according to the influence that they had from medical doctors and nutritionists who gave them lectures. The results of the test given to them showed that out of 249 BHW's 138 have low knowledge on oral health. Only 24 are considered to have high knowledge on oral health while 87 are considered to be in the medium range.category. Their knowledge and practices were also influenced by their occasional consultation or visit to a private dentist, from television commercials and on the common knowledge passed down by their mothers but based on all of this, data, it can be inferred that Barangay Health Workers have knowledge and practices on oral health but was still not enough to teach the constituents under them since they still have misconceptions about oral health and they only do oral health practices based on what they believed was adequate to have a healthy oral cavity. It is hereby recommended that future studies be made to verify the findings of this study and to validate the oral hygiene practices of the BHW's thru oral examination. It is also recommended that a system be made that will evaluate and reinforce what was taught to BHW's regarding knowledge on oral health and to stress the importance of practicing what they know is right.